2021
DOI: 10.5001/omj.2021.71
|View full text |Cite
|
Sign up to set email alerts
|

Featuring Trends in the Epidemiology of Lung Cancer Following the Publication of the National Cancer Strategy in Qatar

Abstract: Objectives: Qatar has witnessed significant reforms in its health care system, including the care of cancer patients. In 2011, the National Cancer Strategy was released with the aim to deliver a high standard of care to cancer patients across the country. We sought to investigate the featuring trends in the epidemiological and clinical characteristics of lung cancer in Qatar following the publication of the National Cancer Strategy. Methods: We conducted a retrospective cohort study documenting the epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our study also showed a 5-year survival rate of 0.1% and a 1-year survival rate of 13.1%; numbers that raise red flags when compared with survival rates worldwide. The most recent 5-year survival rate in the US and in wealthier countries in the Middle East and North Africa region (commonly referred to as MENA) (eg, Qatar) approximated 25%. Our reported survival rates are notably lower than those observed in low-resource countries almost 2 decades ago (8.9%) and in neighboring nations facing political and financial challenges, such as Jordan (approximately 10%) .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed a 5-year survival rate of 0.1% and a 1-year survival rate of 13.1%; numbers that raise red flags when compared with survival rates worldwide. The most recent 5-year survival rate in the US and in wealthier countries in the Middle East and North Africa region (commonly referred to as MENA) (eg, Qatar) approximated 25%. Our reported survival rates are notably lower than those observed in low-resource countries almost 2 decades ago (8.9%) and in neighboring nations facing political and financial challenges, such as Jordan (approximately 10%) .…”
Section: Discussionmentioning
confidence: 99%
“…The most reported cancers were breast, colorectal, prostate, leukemia, and non-Hodgkin lymphoma [6]. As with global trends, it is suspected that mortality for specific types of cancer is also decreasing in Qatar [7][8][9]. Nevertheless, the related burden on patients, healthcare systems, and the economy illustrates that cancer is a significant public health issue in Qatar [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most reported cancers were breast, colorectal, prostate, leukemia, and non-Hodgkin lymphoma [6]. As with global trends, it is suspected that mortality for speci c types of cancer is also decreasing in Qatar [7][8][9]. Nevertheless, the related burden on patients, healthcare systems, and the economy illustrates that cancer is a signi cant public health issue in Qatar [4].…”
mentioning
confidence: 99%